Two new stingrays (Chondrichthyes: Dasyatidae) from the eastern Indonesian Archipelago - Last, Peter R.; White, William T. (Zootaxa, 2013)
Two new stingrays, Dasyatis longicauda sp. nov. and Himantura javaensis sp. nov., are described from material collected in the eastern Indonesian Archipelago. These species, which are both relatively small stingrays (both probably smaller than 40 cm DW), have been confused with closest relatives in the region. Dasyatis longicauda sp. nov., known from West Papua, differs from its congener, the Australian endemic D. fluviorum, in having a slightly lower vertebral count, lower pectoral-radial count, a longer tail, larger and less numerous thorns along the mid-disc and tail, as well as a different CO1 Barcode. Himantura javaensis sp. nov., known only from southern Java (near Cilacap), belongs to a complex of small whiprays which also includes another Indonesian species, H. walga. Apart from major differences in squamation and a different CO1 Barcode, Himantura javaensis is more brownish in coloration, has more vertebrae, a longer tail, smaller eye and orbit, more posteriorly positioned sting, shorter adult claspers, shorter pelvic fin, and differs in various measurements around the head.